The Influence of Foreign Debt, Foreign Investment, Inflation, and Non-Oil and Gas Exports on Indonesia's Economic Growth (1994-2023) - Suci Libernia Gulo; Ida Ayu Gde Dyastari Saskara; I Wayan Priyana Agus Sudharma (International Journal of Economics, Management and Accounting, 2025)
Economic growth is one of the main benchmarks for assessing a country's economic performance over time. Increased and sustainable economic growth are essential requirements for continued economic development. This study aims to explore the impact of foreign debt, foreign investment, inflation, and non-oil and gas exports, both individually and simultaneously, on economic growth in Indonesia. The data used in this study are time series for three decades, from 1994 to 2023. The methodology used in this study is multiple linear regression analysis, which aims to determine the effect of independent variables on dependent variables, both individually and simultaneously. The findings of this study indicate that simultaneously, foreign debt, foreign investment, inflation, and non-oil and gas exports have a significant impact on Indonesia's economic growth during the period 1994 to 2023. Separately (partially), foreign debt and inflation have a significant negative effect on Indonesia's economic growth in the period 1994 to 2023. On the other hand, foreign investment shows an insignificant negative impact on the country's economic growth in the same period. However, non-oil and gas exports have a significant positive impact on Indonesia's economic growth between 1994 and 2023.